2015
DOI: 10.1155/2015/430436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Prophenin 2 on the Integrity and Viability ofTrichomonas vaginalis

Abstract: Trichomonas vaginalis is the causal agent of trichomoniasis, which is associated with preterm child delivery, low birth weight, and an increased risk of infection by human papilloma virus and human immunodeficiency virus following exposure. Several reports have established increasing numbers of trichomoniasis cases resistant to metronidazole, the agent used for treatment, and it is therefore important to identify new therapeutic alternatives. Previously, our group reported the effect of tritrpticin, a syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In this regard, the list of differentially abundant proteins between CFTR +/+ and CFTR -/neutrophils showed that CFTR -/neutrophils were defective in several proteins implicated in neutrophil maturation and response to pathogens. Antimicrobial peptides, such as PR-39 (22) and Prophenin-2 (23), as well as SRGN, PTPRN2 and CANX, which are implicated in phagosome and granule maturation and degranulation processes were downregulated in CFTR -/neutrophils. In addition, we identified several proteins that play an important role in reactive oxygen species (ROS) generation to be differentially abundant in the CFTR -/neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the list of differentially abundant proteins between CFTR +/+ and CFTR -/neutrophils showed that CFTR -/neutrophils were defective in several proteins implicated in neutrophil maturation and response to pathogens. Antimicrobial peptides, such as PR-39 (22) and Prophenin-2 (23), as well as SRGN, PTPRN2 and CANX, which are implicated in phagosome and granule maturation and degranulation processes were downregulated in CFTR -/neutrophils. In addition, we identified several proteins that play an important role in reactive oxygen species (ROS) generation to be differentially abundant in the CFTR -/neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Their structures are stabilized only by hydrogen bonds and van der Waals force of interacting with the membrane lipids. Typically, PR-39 is rich in proline (49%) and arginine (24%) [ 108 ], prophenin-1 is rich in proline (53.2%) and phenylalanine (19%) [ 109 ], indolicidin is rich in tryptophan (38%) and proline (23%) [ 110 ], and histatin-8 is rich in histidine (33.3%) [ 111 ].…”
Section: Structure and Characteristics Of Ampsmentioning
confidence: 99%
“…PF-1 was more effective against Gram-negative bacteria as compared to Gram-positive bacteria [ 145 ]. One study reported that recombinant PF-2 affected the growth and integrity of Trichomonas vaginalis [ 146 ]. In primary bone marrow cells, expression of the PF-2 gene is regulated by cytokines GM-CSF and IL-3 and transcription factor PU.1 [ 147 ].…”
Section: Porcine Ampsmentioning
confidence: 99%